Tinjauan sistematis: Korelasi vitamin D terhadap Sel T regulator pada penderita lupus eritematosus sistemik - Sherly Permata; Aimmatul Fauziyah (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Vitamin D is linked to immunity and autoimmune diseases, including systemic lupus erythematosus (SLE). Autoimmune diseases often involve impaired regulation of regulatory T cells (Tregs). Despite numerous studies exploring the relationship between vitamin D and Tregs in SLE, the findings remain inconclusive.Objectives: To determine whether there is a relationship or correlation between vitamin D and regulatory T cells in patients with systemic lupus erythematosus based on existing research articles employing different research methods.Methods: We conducted a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines from February to May 2024. We sourced articles from Google Scholar, PubMed, and MDPI, focusing on research published between 2014 and 2024. Inclusion criteria were relevance to the topic and availability in full text, while exclusions were animal studies, research older than ten years, and articles not available in full text. Seven articles met the criteria and were reviewed.Results: Out of the seven articles reviewed, five found a correlation between vitamin D levels and the ratio and function of Tregs in SLE patients. Specifically, higher levels of vitamin D were associated with increased suppression of Tregs.Conclusion: The results of studies on vitamin D levels and Tregs in SLE patients are inconsistent. Further evaluation and additional research are required to determine the potential clinical benefits of vitamin D management in SLE therapy.